METODE FUZZY ANALYTICAL HIERARCHY PROCESS DALAM PENGAMBILAN KEPUTUSAN PENYALURAN KREDIT (Studi Kasus Penyaluran Kredit pada PD. BPR BKK Kebumen Cabang Puring) - , EKA SETYANINGSIH; , Dr. Gunardi, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bank is agency that assemble fund from people in saving and distribute it to people in credit or other form. As time goes on after the credit is realized, it canât be denied that bank will facing the risk, that is problematical credit. For example, uncapability to pay interest and return credit at the time to maturity. Therefore, bank have to make dicision appropriately and effectively in credit distribution to prospective borrower. In relation, Analytical Hierarchy Process (AHP) can be used to help solve this problem. AHP is used when the taken decision involve many factors, that decision maker get difficulty in making weight to each factors. So that, AHP can solve a complex situation, unstructured into several component of hierarchy structure, with put on subjective value about the importance of each variable relatively, and decide what variable that has highest priority to influence the result on that situation. Although, the used of AHP in Multi Criteria Decision Making (MCDM) often get criticism because the uncapability of AHP approach to solve unprecisely factor that decision makers feel when give precise value in comparison matrix. Therefore, Fuzzy AHP method is developed to solve the existing weakness of AHP. It is merge of AHP and Fuzzy approach.